Strategic texturation of VO2 thin films for tuning mechanical, structural, and electronic couplings during metal-insulator transitions. (1st January 2023) - Zhang, Yuwei; Fincher, Cole D.; Gurrola, Rebeca M.; Serem, Wilson; Zhao, Dexin; Shin, Jungho; Banerjee, Sarbajit; Xie, Kelvin; Shamberger, Patrick; Pharr, Matt
Abstract: Owing to its pronounced metal-insulator transition at ∼340 K, vanadium dioxide (VO2 ) has emerged as a promising candidate material to emulate neuronal logic and memory functions for neuromorphic computing applications. For viable implementation into practical devices, it is critical to understand the fundamental mechanical behavior of VO2 during this phase transformation. Herein, we implemented sputter deposition under various conditions to strategically texture VO2 thin films, thereby enabling us to examine the influence of crystal orientation on mechanical, structural, and electrical properties across its characteristic metal-insulator transition. Notably, polycrystalline VO2 and epitaxial VO2 /sapphire (0001) films developed tension, whereas epitaxial VO2 /TiO2 (001) developed compression in heating through the phase transformation. Through structural analysis, we attribute this tension/compression disparity to highly anisotropic deformation that occurs during the phase transformation. Corresponding analyses from linear elastic fracture mechanics enable the prediction of a critical film thickness, below which polycrystalline VO2 films will not fracture, which has implications for the design of resilient neuromorphic architectures. Similarly, by analyzing the stress evolution in epitaxial VO2 /TiO2 (001) films, we find that fracture occurs during sputter deposition itself. Finally, we conduct simultaneous measurements of mechanical stress and electrical conductance of polycrystalline and epitaxial VO2 thin films during thermal cycling. Surprisingly, we unveiled that the orientation of the film can even alter the temperature-sequence of the macroscopic electrical response and overall stress response during the phase transformation, which we attribute to spatial heterogeneities in the transformation. Graphical abstract: Image, graphical abstract